1020 Delay to Surgery in Acute Perforated and Ischaemic Gastrointestinal Pathology. (12th October 2021) - Murray, V; Burke, J; Hughes, M; Schofield, C; Young, A
Abstract: Introduction: Patients with acute abdominal pathology requiring emergency laparotomy who experience a delay to theatre have an increased risk of morbidity, mortality, and complications. The timeline between symptom onset and operation is ill-defined with international variance in assessment and management. This systematic review aims to define where delays to surgery occur and assess the evidence for previous interventions. Method: A systematic review was performed searching MEDLINE and EMBASE databases (January 1 st 2005 to May 6 th 2020). All studies assessing the impact of time to theatre in patients with acute abdominal pathology requiring emergency laparotomy were considered. Results: Eighty-five results were assessed to include 19 papers in the analysis. Fifteen unique timepoints were identified in the patient pathway between symptom onset and operation which could be classified into four distinct phases. Time from admission to theatre (1 to 72 hours), and mortality rate (10.6-74.5%) varied greatly between studies. Mean time to surgery was significantly higher in deceased patients compared to survivors. Delays were related to imaging, diagnosis, decision-making, theatre availability and staffing. Four of five interventional studies showed a reduced mortality following introduction of an acute laparotomy pathway. Conclusions: There is wide variation in the definition and measurement of time delays prior to emergency surgery with few studies exploring interventions. Given the heterogenous nature of the patient population and pathologies, an assessment and management framework from onset of symptoms to operation is proposed. This could be incorporated into national mortality prediction and audit tools and assist in the assessment of interventions.